Censorship: Media/CSO websites, Proton VPN (Venezuela) - Voidly (2024)
CRITICAL severity censorship detected in Venezuela. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: VE-2024-0002
Keywords: censorship; VE; censorship; critical